2019
DOI: 10.1097/md.0000000000014097
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes of a cervical cage with integrated fixation

Abstract: Cervical cages with integrated fixation have been increasingly used in anterior cervical discectomy and fusion (ACDF) to avoid complications associated with anterior cervical plates. The purpose of this paper is to provide 2-year follow-up results of a prospective study after implantation of a cervical cage with an integrated fixation system.This was a prospective multicenter outcome study of 90 patients who underwent ACDF with a cage with integrated fixation. Fusion was evaluated from computed tomography imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The ROI-C device system, an anatomical PEEK cage and two VerteBRIDGE self-locking plates, is designed for the elimination of the basic disadvantage of stand-alone cage. 17 Multiple studies, 17 18 22 23 28 30 33 including our study, showed low subsidence rate. Most patients with cage subsidence did not experience any symptoms and they achieved fusion in the final follow-up.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The ROI-C device system, an anatomical PEEK cage and two VerteBRIDGE self-locking plates, is designed for the elimination of the basic disadvantage of stand-alone cage. 17 Multiple studies, 17 18 22 23 28 30 33 including our study, showed low subsidence rate. Most patients with cage subsidence did not experience any symptoms and they achieved fusion in the final follow-up.…”
Section: Discussionmentioning
confidence: 49%
“…However, postoperative cage subsidence should be aware in patients with multilevel ACDF using selflocking stand-alone cage. 34,35 According to the study of 90 patients who underwent ACDF with the ROI-C device by Lonjon et al, 22 they reported anchoring plate fracture in 5 (2%) from 249 plates with no clinical consequence. The mechanism of anchoring plate fracture remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various analysis has equated the radiological and clinical outcomes of cage-andplate fixation and cage-only practices [7][8] . In few analyses, lower subsidence rates and higher fusion percentage is noticed with cage-and-plate fixation while additional analyses exhibited no alteration among the two techniques 9 . In newly published metaanalysis, no differences in radiological and clinical results were found amid the cage and fixation of plate and cage-only group at ACDF 1-level surgery [10][11] .…”
Section: Introductionmentioning
confidence: 91%
“…The incidence of postoperative dysphagia in patients undergoing ACDF with zero-profile stand-alone cervical cages has been reported as 3.7% [57]. ACDF with the use of zero-profile intervertebral cages has shown a rate of transient postoperative dysphagia at 1.1%-7.9% [58][59][60][61][62]. Among 25 patients treated with ACDF with a zero-profile cage, three patients presented with mild transient dysphagia that resolved at two weeks and two patients had moderate dysphagia that resolved at five weeks [63].…”
Section: Acdf Devices and Disc Replacementmentioning
confidence: 99%